Effect of retorting and oven cooking on the nutritional properties of beef frankfurters blended with palm oils - Wan Rosli, W. I.; Babji, A.S.; Aminah, A.; Foo, S. P.; Abd. Malik, O. (Taylor & Francis, 2010)
The effect of retorting and oven cooking on the nutritional properties of beef frankfurters blended with palm oil (PO), red PO35 and red PO48 were compared against the control beef fat treatment. Red PO oven-cooked beef frankfurters resulted in a significant loss of vitamin E from 538.5 to 287.5 mg after 6 months. Oven cooked sausages stored at –18C and retorted sausages stored for the 6 months of shelf studies resulted in more than 90% loss of a-carotene and b-carotene in red PO beef frankfurters. Cholesterol was reduced at the range of 29.0–32.2 mg/ 100 g when beef fat was substituted with palm-based oils, in beef frankfurters. Differences of heat treatments did not significantly change THE cholesterol content, within all treatments. This study showed the potential of utilizing red palm oils as animal fat analogues in improving vitamin E, reducing cholesterol but not carotenes in beef frankfurters.